The Effects of Rice Flour Solution and ZnO Nanoparticles Coated on Mango to Inhibit Anthracnose Disease - Abdullah, Saifollah; Rosman, NF.; Asli, NA.; Rusop, Mohamad (International Journal of Engineering and Technology, 2019)
Nowadays nanotechnology is used in many applications including electronic devices, sensor, solar cell, pharmaceutical and food and agriculture industry as well. One of the main contributions of nanotechnology in agrotechnology industry is preservation of post-harvest product through coating process. A mango fruit is very perishable and so has a short shelf life, which both marketers and consumers would like to be longer. In this study, mango fruit was coated with ZnO and rice flour solution of 3 mg/ml and 5 mg/ml manually and was stored at room temperature for 7 days to observe the growth of black spot daily. The weight loss was also evaluated. The mixed coating materials which is ZnO and rice flour inhibited the growth of microorganisms. The results in SEM show that the nanoparticles agglomerates. The data revealed that applying ZnO coating effectively prolonged the quality attributes and extends the shelf life of mango fruit.Â Â Â